Frequency and Clinical Manifestations of Dengue in Urban Medellin, Colombia. (29th May 2014) - Restrepo, Berta Nelly; Beatty, Mark E.; Goez, Yenny; Ramirez, Ruth E.; Letson, G. William; Diaz, Francisco J.; Piedrahita, Leidy Diana; Osorio, Jorge E.
Abstract : A dengue fever surveillance study was conducted at three medical facilities located in the low-income district of San Javier in Medellin, Colombia. During March 2008 to 2009, 781 patients with fever regardless of chief complaint were recruited for acute dengue virus infection testing. Of the 781 tested, 73 (9.3%) were positive for dengue infection. Serotypes DENV-2 (77%) and -3 (23%) were detected by PCR. One patient met the diagnostic criteria for dengue hemorrhagic fever. Only 3 out of 73 (4.1%) febrile subjects testing positive for dengue infection were diagnosed with dengue fever by the treating physician. This study confirms dengue virus as an important cause of acute febrile illness in Medellin, Colombia, but it is difficult to diagnose without dengue diagnostic testing.